FABRICATION AND CHARACTERIZATION OF BREAST PHANTOM BASED ON GELATIN-GLYCERIN-TiO2 FOR A CONTINUOUS-WAVE DIFFUSE OPTICAL TOMOGRAPHY - Ukhrowiyah, N.; Hikmawat, D.; Yasin, M.; Yuni, R. (Malaysian Journal of Science, 2019)
In this paper, the fabrication and characterization of breast phantom based on gelatin-glycerin-TiO2 as breast simulation tissue is proposed and investigated. A sample preparation was done by mixing 3 grams of gelatin per 10 ml of saline. The sample was added with glycerin with four different concentrations of 85%, 90%, 95% and 100% as sample A, B, C and D respectively. The sample D is optimum as it was able to survive at room temperature for 126 hours. Subsequently, sample D was added by TiO2 given variations of 0.010 grams, 0.015 grams, 0.020 grams and 0.025 grams. All samples were tested for its homogeneity and absorption coefficient using Continuous Wave Diffuse Optical Tomography (CW-DOT) with laser wavelengths of 780, 808 and 830 nm. The results showed that the optimum sample characterization was achieved at wavelength of 830 nm with TiO2 variation of 0.025 grams. The absorption coefficient breast phantom was obtained at 0.167 mm-1. Phantom based on gelatin-glycerin-TiO2 can be applied as material replacement of breast for test object in CW-DOT.